Development of Mini Cinema Digital Media in Science Learning on the Material of my Region, my Pride in Class V of Kerokan Elementary School - Vera Yulia Veriska; Fitria Dwi Prasetyaningtyas (Postgraduate, University of Mataram, 2025)
This study aims to develop media, test the feasibility, and determine the effectiveness of mini cinema digital media, in the subject of science, my proud region. This mini cinema digital media is a media that refers to the concept of utilizing space or audiovisual devices that will later display videos or films, and other audiovisual materials to support learning. This study uses development research or R&D (Research and Development) which uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. In the subject section for this research data, 24 students of grade V of Kerokan Elementary School, Temanggung Regency were used. The data collection techniques used were media expert validation questionnaires, material expert validation questionnaires, student response questionnaires and teacher response questionnaires. With the results of media expert validity based on media expert assessments of 88% and material expert validation of 84% with the category